2017
DOI: 10.18632/oncotarget.15646
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-143-3p, up-regulated in H. pylori-positive gastric cancer, suppresses tumor growth, migration and invasion by directly targeting AKT2

Abstract: Our previous studies have suggested a protective role for H. pylori infection in the prognosis of gastric cancer. Based on those findings, we hypothesized that H. pylori-positive and -negative gastric cancers may exhibit different growth patterns and pathobiological behaviors, indicating different mechanisms of cancer progression. By microarray analysis, we studied miRNAs expression profiles in 42 gastric cancer patients, comparing 21 H. pylori-positive and 21 H. pylori-negative groups. Luciferase reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…miR-143-3p was reported to be upregulated in H. pylori-positive gastric cancer, and it suppressed tumor proliferation, migration, and invasion by directly targeting AKT2. 17 However, miR-143-3p was also found to be downregulated in esophageal squamous cell carcinoma and ovarian carcinoma, and it contributed to cancer progression. 17,30,31 miR-143-3p was induced by p53, and an excess of miR-143-3p prevented the induction of MDM2, BTG2, and CDKN1A mRNA and/or protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-143-3p was reported to be upregulated in H. pylori-positive gastric cancer, and it suppressed tumor proliferation, migration, and invasion by directly targeting AKT2. 17 However, miR-143-3p was also found to be downregulated in esophageal squamous cell carcinoma and ovarian carcinoma, and it contributed to cancer progression. 17,30,31 miR-143-3p was induced by p53, and an excess of miR-143-3p prevented the induction of MDM2, BTG2, and CDKN1A mRNA and/or protein.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that six miRNAs, miR-2392, miR-362-5p, miR-193a-5p, miR-143-3p, miR-493-5p, and miR-600, were closely associated with invasion and cancer metastasis. [14][15][16][17][18][19] Then we used qRT-PCR to validate the expression levels of six miRNAs in SACC cells after transfection. Our results showed that the expression levels of miR-193a-5p and miR-143-3p were significantly upregulated in SACC-LM cells when ADAMTS9-AS2 was deleted, yet miR-193a-5p and miR-143-3p were downregulated in SACC-83 cells when ADAMTS9-AS2 was overexpressed, indicating a potentially competing relationship between the ADAMTS9-AS2 and miR-193a-5p or miR-143-3p ( Figures S2A and S2B).…”
Section: Adamts9-as2 Binds Mir-143-3p and Depresses Its Expressionmentioning
confidence: 99%
“…MicroRNAs are known to carry out their biological functions through regulating the protein expression of downstream target genes, thus affecting the occurrence and development of tumors. To date, a number of possible target genes have been identified for miR-143-3p including quaking I-5 protein (QKI-5), 13 AKT serine/threonine kinase 2 (AKT2), 14 mitogen-activated protein kinase 7 (MAPK7), 15 and DNA methyltransferase 3A (DNMT3A). 16 In this study, we used bioinformatics software to predict 108 possible target genes of miR-143-3p and by real-time quantitative PCR confirmed that the expression levels of both As a transmembrane glycoprotein-adhering receptor, ITGA6 mediates cell-matrix and cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Among 53 different miRNAs, the expression of miR‐143‐3p was the most significantly upregulated in H. pylori (+) gastric cancer tissues. In vitro assays revealed a negative regulation on cell growth, apoptosis, invasion, and migration, showing that miR‐143‐3p acts as tumor suppressor miRNA by targeting AKT2 . Regarding H. pylori ‐related virulence factors, Zou et al.…”
Section: Deregulation Of Host Functionsmentioning
confidence: 99%
“…In vitro assays revealed a negative regulation on cell growth, apoptosis, invasion, and migration, showing that miR-143-3p acts as tumor suppressor miRNA by targeting AKT2. 46 Regarding H. pylori-related virulence factors, Zou et al demonstrated that Tipα, a carcinogenic factor of H. pylori, activated NF-κB by inhibiting the miR-3178-mediated targeting of TRAF3. 47 MiR-124 has tumor suppressive functions and is regulated by CpG methylation silencing.…”
Section: H Pylori Infection and Autophagymentioning
confidence: 99%